A Smartphone App for Increasing Live Organ Donation. Issue 12 (10th August 2016) - Kumar, K.; King, E. A.; Muzaale, A. D.; Konel, J. M.; Bramstedt, K. A.; Massie, A. B.; Segev, D. L.; Cameron, A. M.
Abstract : The incidence of live donor transplantation has declined over the past decade, and waitlisted candidates report substantial barriers to identifying a live donor. Since asking someone to donate feels awkward and unfamiliar, candidates are hesitant to ask directly and may be more comfortable with a passive approach. In collaboration with Facebook leadership (Facebook Inc., Menlo Park, CA), we developed a mobile application—an app—that enables waitlisted candidates to create a Facebook post about their experience with organ failure and their need for a live donor. We conducted a single‐center prospective cohort study of 54 adult kidney‐only and liver‐only waitlisted candidates using the Facebook app. Cox proportional hazards models were used to describe donor referral on behalf of candidates using the app compared with matched controls. The majority of candidates who used the app reported it to be "good" or "excellent" with regard to the installation process (82.9%), readability (88.6%), simplicity (70.6%), clarity (87.5%) and the information provided (85.3%). Compared with controls, candidates using the Facebook app were2.43 6.6117.98 times more likely to have a donor come forward on their behalf (p < 0.001). The Facebook app is an easy‐to‐use instrument that enables waitlisted candidates to passively communicate with their social network about their need for a live donor. Abstract : The authors find a Facebook‐based smartphone app developed to facilitate patient storytelling and identification of potential appropriate living donors easy and simple to use, and effective in increasing donor identification.